PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN BUAH MELON PT. SYAFINA NIAGA - Slamet Istoto; Iwan Kurniawan Subagja (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
Decision making is an individual activity that is directly involved in obtaining and using the goods offered. Promotion is one of the variables in a marketing mix that is very important to be implemented by a company in marketing its products or services, thus influencing consumers to make purchasing decisions. The quality of the product can also affect consumers in making purchasing decisions. This study aims to analyze the effect of product quality and promotion on purchasing decision of Melon fruit. Population and sample of research is purchasing or buyer from consumer of PT. Syafina Niaga as many as 30 companies and sampling methods using saturated sampling techniques as well as analysis used with regression analysis. The results showed that there is a significant influence between product quality and promotion of purchasing decisions.